Engineering soft-hard tissue interfaces in dental and craniofacial system by spatially controlled bioactivities - Hun Jin Jeong; Lan Anh P. Hoang; Neeve Chen; Elen Zhu; Albert Wang; Bozhi Chen; Emma Y. Wang; Christopher L. Ricupero; Chang H. Lee (Bioactive Materials)
The interface between soft and hard tissues is constituted by a gradient change of cell types and matrix compositions that are optimally designed for proper load transmission and injury protection. In the musculoskeletal system, the soft-hard tissue interfaces at tendon-bone, ligament-bone, and meniscus-bone have been extensively researched as regenerative targets. Similarly, extensive research efforts have been made to guide the regeneration of multi-tissue complexes in periodontium. However, the other soft-hard tissue interfaces in the dental and craniofacial system have been somewhat neglected. This review discusses the clinical significance of developing regenerative strategies for soft-hard tissue interfaces in the dental and craniofacial system. It also discusses the research progress in the field focused on bioengineering approaches using 3D scaffolds equipped with spatially controlled bioactivities. The remaining challenges, future perspectives, and considerations for the clinical translation of bioactive scaffolds are also discussed.